Preoperative Percutaneous Transthoracic Needle Biopsy Increased the Risk of Pleural Recurrence in Pathological Stage I Lung Cancer Patients With Sub-pleural Pure Solid Nodules. (13th September 2016) - Kashiwabara, Kosuke; Semba, Hiroshi; Fujii, Shinji; Tsumura, Shinsuke
ABSTRACT: We retrospectively evaluated whether preoperative percutaneous transthoracic needle biopsy (PTNB) affected the incidence of pleural recurrence in pathological stage I lung cancer patients. Pleural recurrence occurred in pure solid nodule (PSN) cases but not in ground-glass nodule cases, as evaluated using thin-section computed tomographic imaging. When the cases were restricted to sub-pleural PSN, the incidence of recurrence tended to be higher in a PTNB group (63 patients diagnosed by PTNB) than in a non-PTNB group (86 patients diagnosed by transbronchial biopsy or intraoperative diagnosis) (25% vs. 4%, p =.050). PTNB should not be performed in patients with a sub-pleural PSN.